2006
DOI: 10.1007/bf02898451
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of inflammatory bowel diseases in childhood

Abstract: Inflammatory Bowel Disease (IBD) is common in most industrialised countries and childhood IBD accounts for nearly 30% of total cases. Various studies, mostly from Europe and USA have reported epidemiological characteristics of childhood IBD. The incidence figures vary greatly from region to region and within a region over time. Almost all reported studies have documented an increase in the incidence, mainly of Crohn's disease over the last few decades. The reasons for the increase are not clear but epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…17 Studies in pediatric patients have suggested early onset disease (age 0–5 years) may represent a different disease phenotype. 5,18,19 In a previous study, we found that children who are older at diagnosis (6–17 years) are at higher risk for the development of complicated disease compared with children who are younger at diagnosis (0–5 years). 2 Therefore, adjusting the classification system further to create an age category for patients diagnosed at 0–5 years may be beneficial.…”
Section: Discussionmentioning
confidence: 93%
“…17 Studies in pediatric patients have suggested early onset disease (age 0–5 years) may represent a different disease phenotype. 5,18,19 In a previous study, we found that children who are older at diagnosis (6–17 years) are at higher risk for the development of complicated disease compared with children who are younger at diagnosis (0–5 years). 2 Therefore, adjusting the classification system further to create an age category for patients diagnosed at 0–5 years may be beneficial.…”
Section: Discussionmentioning
confidence: 93%
“…The current mean prevalence of IBD in the general population of Western countries is estimated at 1/1,000 inhabitants [25, 26]. Although there are only few epidemiologic data available regarding developing countries, the disease's incidence and prevalence seem to be increasing over the past 50 years in practically all regions of the world, indicating its emergence as a global disease [27, 28]. The trend appears to have stabilised for the adult population but not for the paediatric one, especially in Central and Southern Europe where it appears to be rising [29, 30].…”
Section: Ibd Epidemiology Worldwide: Data Regarding the General Anmentioning
confidence: 99%
“…Prior reports suggest that early-onset IBD differs epidemiologically and is characterized by predominant colonic involvement and a high positive family history compared to older age of onset (10, 11). Another study reported a high proportion of colonic and perianal disease in early-onset CD (12).…”
Section: Introductionmentioning
confidence: 99%